The limits of patience: building, mobilising and bounding patient capital in family SMEs across a polycrisis - Michael Kuttner; Thomas Rudolf Mörth; Julia Riepl (Journal of Family Business Management, 2026)
Purpose This study investigates how small and medium-sized family firms (family SMEs) build, mobilise and bound patient capital over the 2020–2024 polycrisis and how socioemotional wealth orders the financing hierarchy they follow. Design/methodology/approach An exploratory, abductive multiple-case study of 18 Austrian family SMEs (21 informants) pairs framework-based thematic analysis of semi-structured interviews with register-based archival triangulation, setting self-reported financing behaviour against indicators drawn from annual statements and the company register. Findings Firms build patient capital in stable periods through retention and reserve-holding, then draw it down once the crises hit while leaning on a trusted house bank for bridging credit. Financing follows a socioemotional order: internal funds first, the house bank second, distrusted state support a distant third and external equity all but ruled out. The conservatism that buffers a firm can equally starve it of investment, so patience proves an asset only under particular conditions. Research limitations/implications The sample is of surviving firms in a bank-based economy and the data are retrospective; the findings are analytically, not statistically, generalisable and invite longitudinal and supply-side extension. Practical implications Owner-managers and successors can manage patient capital deliberately, through retention rules, rolling liquidity forecasts, staged investment and more than one cultivated house-bank tie; advisors, lenders and policymakers should weigh soft signals of resilience and the value of dependable crisis instruments and locally embedded banks. Originality/value The study recasts patient capital as a dynamic, bounded resource whose value is non-monotonic rather than a uniformly beneficial static endowment, extends the pecking order into an SEW-augmented financing hierarchy for family SMEs and shows how register-based archival triangulation provides partial corroboration for claims of financial conservatism.